Revision of the fern genus Diplazium (Polypodiales: Athyriaceae) in Thailand - Pongkai, Puttamon; Zhang, Li-Bing; Boonkerd, Thaweesakdi; Pollawatn, Rossarin (Phytotaxa, 2023)
The genus Diplazium in Thailand is revised. Thirty-one species are recognized, of which D. thailandicum is new to science, and two species, D. bellum and D. pallidum are new to Thailand. These species are described and illustrated. The lectotypes of D. dilatatum, D. leptophyllum, D. petolotii and D. petrii are designated here. A key to the species, descriptions, line drawings, and ecological and distributional information are provided.